1996
DOI: 10.1103/physrevb.53.16027
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the soldering reaction between eutectic SnPb alloy and Cu accompanied by ripening

Abstract: The wetting reaction of molten eutectic SnPb on Cu leads to Cu-Sn intermetallic compound formation, but not compounds of Cu-Pb since they do not exist. Cu-Sn compounds do not form layered structures between the solder and Cu, rather the Cu 6 Sn 5 phase has grown as scalloplike grains into the molten solder. The scalloplike grains grow larger but fewer with time, indicating that a ripening reaction has occurred among them. However, the ripening is not a constant volume process since it is accompanied by the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
249
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(272 citation statements)
references
References 22 publications
14
249
1
Order By: Relevance
“…Generally speaking, the interface between the solder and the IMC, rather than that between the IMC and the substrates, is always rough because it is the foreland of the reaction. 30 However, the opposite result was obtained in our research. Firstly, some Sn-rich regions were found under liquid-state conditions, which is different from the interfacial reactions between most lead-free (e.g., Sn-In) solders and Ag substrates, 24,26,31 as displayed in Fig.…”
Section: Interfacial Reactions Between Sn-4ag-7zn and Agcontrasting
confidence: 56%
“…Generally speaking, the interface between the solder and the IMC, rather than that between the IMC and the substrates, is always rough because it is the foreland of the reaction. 30 However, the opposite result was obtained in our research. Firstly, some Sn-rich regions were found under liquid-state conditions, which is different from the interfacial reactions between most lead-free (e.g., Sn-In) solders and Ag substrates, 24,26,31 as displayed in Fig.…”
Section: Interfacial Reactions Between Sn-4ag-7zn and Agcontrasting
confidence: 56%
“…Thus, sharp edges in a faceted prism-type g-Cu 6 Sn 5 crystal tend to dissolve to minimize the curvature effect (surface area) to form the round scallop-shaped morphology via the coalescence process-Ostwald ripening. 23 Thermomigration is one of the simultaneous heat and mass transfer phenomena that occurs in a mixture, as a result of an external temperature gradient imposed across the mixture. The thermomigration flux J TM of Cu atoms under a temperature gradient dT/dx can be written by…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These works suggest that, upon contact, Cu and liquid Sn react to form two distinct IMCs [Cu 6 Sn 5 (g phase) and Cu 3 Sn (e phase)], which precipitate at different stages of the soldering reaction. Most research seems to suggest that, at the very early stages of the soldering reaction, the g phase precipitates first.…”
Section: Introductionmentioning
confidence: 99%
“…19 Earlier works have focused on experimental characterization of the late stages of growth and coalescence of g and e phases during lead-free soldering reactions between Sn and Cu. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] More recently, several groups have investigated the formation of the g phase at the early stages of soldering reactions. [20][21][22][23] These latter works have found that individual Cu 6 Sn 5 grains seem to appear at random positions along the (metastable) solid/liquid interface within a few milliseconds.…”
Section: Introductionmentioning
confidence: 99%